DAMPAK LITERASI KEUANGAN TERHADAP KINERJA DAN KEBERLANJUTAN UMKM (Studi Kasus Industri F&B Kecamatan Sumbersari Jember) - Muhammad Ilham Naufal; Purwanto, Eko (Profit: Jurnal Adminsitrasi Bisnis, 2022)
With the economic situation in an era of uncertainty, many policy changes and the pandemic, MSMEs have become one of the hopes in meeting the acceleration of economic recovery in Indonesia. The MSME sector is one of the drivers of the economy, but in its current development there are still unresolved problems, one of which is in the financial sector. The purpose of this study was to determine the effect of understanding the financial management of MSME actors on business performance and business sustainability of MSME actors in Jember, East Java, precisely in Sumbersari District. The population in this study are business people with various focuses on the Food & Beverage industry. Sampling was carried out using a non-probability sampling method with saturated sampling type, with the number of respondents being studied as many as 35 respondents. While the data processing technique used is Pertial Least Square (PLS). Based on the results of the study, it can be concluded that Financial Literacy does not contribute to Business Performance and Business Sustainability at MSMEs in Jember Regency. However, Performance still shows its influence on Business Continuity.